Desain Inverter 1 Fasa Pada Pembangkit PV 9 X 10 WP Menggunakan Metode SPWM Dengan Sistem Kontrol Arduino - Jhon Lodewyik Situmeang; Antonius Rajagukguk; Eddy Evrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
There were several alternatives that can be used to generate electrical energy, one of the ways is by using solar cells, to fulfill the needs of electrical energy. This solar cells utilization very fit with indonesia climate because indonesia has tropical climate, where the sun shines all year round. Not only that, this energy is renewable, clean and environmentally friendly. In other words this energy inexhaustible and safe as long as the sun can shine. The generator that can be used to produce electrical energy called PV, as it is known, PV itself is a generator that produces DC electricity. In this situation, an inverter is needed to be able to convert DC to AC, because all properties used at home require AC power. In this research the researcher use a PV generator source with 90 Watt-Peak power, therefore the inverter is made to adjust the capacity of the PV generator, where the switching process uses the IRF44n type mosfet, with the mosfet driver using IC type IR2110, where the switching process is itself controlled by Arduino with the SPWM method. so that the output of the inverter is an AC voltage with a frequency of 50HzKeywords : PV, Arduino, Switching, Inverter